Improving the Quality of Education Through Academic Culture at SMP Islam Sabilurrosyad Malang - Moh Eko Nasrulloh; Imam Safi'i; Faridatus Sa’adah (Tadbir : Jurnal Studi Manajemen Pendidikan, 2021)
Quality educational institutions have a vision to produce graduates who are competent and able to compete in the future. To achieve the vision of educational institutions, various programs are needed to produce graduate competencies. Academic culture is a supporting factor to produce quality graduates. Meanwhile, in the application of academic culture there are various obstacles that occur. Therefore, the purpose of this study is to describe how to plan the development of academic culture in schools. How to implement academic culture according to plan. and how the influence of academic culture on the competence of graduates. Qualitative Method Case studies are used to examine quality improvement through academic culture at Sabilurrosyad Islamic Junior High School. Collecting data through observation, interviews, and documentation. The results of the study indicate that planning for the development of academic culture is carried out by developing several factors that influence academic culture and the management of academic culture. Implementation is used in an academic culture with school review and benchmarking in all programs. Meanwhile, quality assurance and quality control are carried out in most programs. The impact on graduate competence from the application of academic culture is that students can play a very good role in critical, creative, constructive, dialogical, partnership, productive aspects and appreciate achievements.